Comprehension-promoting strategies: the sum of the parts and the whole - Gissi Sarig (Ilha do Desterro)
Previous research on reading for academic purposes has concentrated on strategies characterizing "the good" and "the poor" reader. Using various methods, researchers have tried to identify sets of strategies, which lead readers to success or failure in academic reading. This approach seems to assume that a given set of strategies may account for success or failure in reading, and that "poor" readers may be trained to adopt "good" reading behavior once they adopt the recommended set of strategies. Contrary to this approach, an in-depth mentalistic study of ten university candidates (Sarig, in press ) showed that readers differ in the sets of strategies which allow them to either succeed or fail in high-level reading tasks.